(untitled) (International Journal of Physiotherapy, 2015)
Background: 6Minute walk test (MWT) has been used as a performance based measure of functional exercise capacity in all populations including healthy adults. 6MWT is recommended out of other all timed walked tests due to its reproducibility and ease of administration compared to other longer or shorter time duration tests. It detects changes following interventions to improve exercise tolerance in healthy individuals, to assess the fitness level, used as intervention to improve walking endurance and as predictor of objectively measured aerobic fitness in healthy adults. It is essential to know a level of fitness healthy adults possess in our community, thus aim of this study was to evaluate response to 6MWT in young healthy adults. Method: 50 healthy individuals (25 males and 25 females) of 18 - 30 years of age were recruited. The 6MWT was performed as per standard guidelines. All subjects were assessed for the outcome measures by principal investigator at baseline i.e. before and post- 6MWT for following parameters. BP, PR, RR, SPO2, RPE. Results: The mean 6 minute walked distance (6MWD) was 635.6+59.07, for men it was 675.0+46.88 and for women it was 596.5+41.41. Out of study population 18% of people covered 70%-80%, 54% people covered 80%-90% and 28% people covered 90%-100% of their predicted distance. Oxygen saturation remained unaltered throughout the walk. Mean resting and walking spo2 values were 96.80+13.55% and 96.71+13.55% (p-value: 0.2288). Pulse rate (PR) and respiratory rate (RR) were affected by the walk. Mean resting and walking PR was 79.82+9.18 and 142.6+19.62 (p-value: 0.0001) and RR was 18.48+2.78 and 30.20+4.35 (p-value: 0.0001) respectively. Mean resting and walking systolic and diastolic blood pressure was significantly higher in males as compared to females. Conclusion: The 6 minute walk test is a useful measure of functional capacity in healthy adults. There was a difference between predicted distance covered and actual distance covered at the end of 6 minute walk test in study population. There was a significant difference between responses of males and females elicited during 6 MWT.